(3UQa GdQjM GdfJf Yf eSJYed GdJJfs - (3OGhhO Hf SdjeGf GdHZOGOjs
(3ChdgG (B:s
(3GdMeO ddg GdPi fRgfG fJf GdJJf hbOQg hfhgfG ai QjGV GdPcQ YfO GfbjGV GdUOQ HJhajbg hbOQg s
(3BNQgG (B:s
(3YGafG Gddg hEjGce ef gPG GdOGA hGdMeO ddg Cgd GdeLO hGdKfGA HdG GfbWGY hdG GfKfGA hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs